Maturação, germinação e desenvolvimento inicial de plântulas de sabiá (Mimosa caesalpiniifoliabenth) - Freitas, Narjara Walessa Nogueira de (2012)
Germination and vigor expression of a seed lot, depends both on factors intrinsic to the plant (such as numbness and physiological maturity), as well as extrinsic factors (proper range of temperature, substrate suitable amount of water and light). Being extremely important to know the factors that influence seed germination, so they can be controlled and manipulated to optimize the percentage, speed and uniformity of germination, resulting in production of more vigorous seedlings for planting and minimizing expenses. In this sense, experiments were carried out to evaluate: a) the effect of different maturation stages on physiological dormancy, germination and vigor of Mimosa caesalpiniifoliaBenth. b)the effect of temperature and substrate on the germination Mimosa caesalpiniifoliaBenth.seed. and to define the best methodology for conducting germination tests with this species; c) the effect of different substrates in the emergence and initial seedling development of Mimosa caesalpiniifoliaBenth. The experiments were conducted at the Laboratory of Seed Analysis (LAS) and in the greenhouse of the Department of Plant Sciences of the Universidade Federal Rural do Semi-Árido (UFERSA). The statistical design was completely randomized (CRD), in experiment I adopted the 2x5 factorial arrangement (with and without dormancy x five maturity stages), constituting 10 treatments, in the second experiment a 2x3 factorial, with two substrates (paper roll and on paper), three temperatures (25ºC, 30ºC and 35ºC), thus six treatments and in experiment III treatments were composed of nine different substrates (T1: vermiculite, T2: coconut fiber, T3: trade Hortimix®, T4: vermiculite, coconut fiber and organic compounds (1:1:1), T5: coconut fiber and compost (1:1), T6: coconut fiber and compost (1:2), T7 vermiculite and compost (1:1), T8, vermiculite and compost (1:2) and T9: organic compound). All treatments were represented by four replications of 25 seeds. Data were submitted to Tukey and Scott-Knott tests at 5% probability. In the first experiment, it was found that the seed robin become dormant as decrease their moisture content and physiologically mature. The higher physiological quality and vigor of seeds are obtained during the ripening and drying of the seed, since dormancy processes are conducted; in experiment II, germination and vigor of thrush was much influenced by temperature, as the substrate used for germination, and the use of rolled paper at a constant temperature of 30°C most suitable for driving the germination, in experiment III, it was found that for good emergence and early development of seedlings robin can be used coconut fiber substrates, commercial hortimix® or vermiculite, and is not recommended to use the organic compound alone or in mixtures